The Consequences of Bullying: Analyzing Its Effects on Student Achievement and Psychological Well-Being - M, Syahruddin; Pongpalilu, Fien; Aisyah, Sitti; Maing, Rosmawati Abdul; Purnamasari, Feby (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Bullying has become a widespread issue in schools, with significant consequences for the victims. This study aims to explore the detrimental effect of bullying on students' academic achievement and stress levels. the study used mixed method approach, combining quantitative and qualitative data.A quantitative approach was employed, with data collected from 223 students at SMA Negeri 1 Pangkep using a Likert scale instrument. The findings reveal that bullying behavior, which encompasses students' thinking, feelings, attitudes, actions, and responsibility, is generally in the "good" category. However, the study also found a significant negative correlation between bullying and student achievement, as well as a positive correlation between bullying and student stress levels. The qualitative results found that bullying effects the students in learning and concentrate at school. This study underscores the importance of addressing bullying in schools to support student well-being and academic success. These results highlight the importance of addressing bullying in schools to ensure a safe and supportive learning environment for all students.